Sosialisasi Pemupukan Berimbang Spesifik Lokasi Untuk Tanaman Jagung Di Kabupaten Dompu - Lolita Endang Susilowati; Bambang Hari Kusumo (Jurnal Gema Ngabdi, 2019)
Farmers' understanding of how to fertilize efficiently and effectively is not yet fully mastered. Most farmers often fertilize crops beyond the recommended dosage. This community service aims to (1) increase farmers' understanding and knowledge of the quality of fertilizers and balanced fertilization technology to achieve the use of fertilizers that are relatively efficient, (2) disseminating balanced fertilization technology with the correct rules. This activity was started with an explanation of fertilizer and balanced fertilization technology, then continued with a balanced fertilization demonstration in Mumbu Village, Woja Subdistrict Dompu District in the planting season of MK 1 in 2018. As the target partner was the Bina Baru Farmer group, Mumbu Village, Woja Subdistrict, Dompu District and as a working partner is a local agricultural extension agent (PPL). The community service team acts as a facilitator, while the local PPL is tasked with assisting the farmers' demonstration activities. This community service activity uses a participatory approach starting from the beginning to the end of the activity in making decisions. The results of community service activities show as follows (1) there is an increase in farmers' understanding of the quality of fertilizers and determination of fertilizer application based on fertilizer quality in applying the site-specific balanced fertilization concept and (2) mastering the application of balanced fertilizer application technology with the 5 T. rule. The application of proven balanced fertilization technology can increase yields from 9 tons per ha (how to fertilize farmers) to 12 tons per ha